214k views
25 votes
F(x) = x4 - 9x3 - 8x2 - 9x - 2; f(-3)
-

2 Answers

9 votes

Answer:


F(-3)=142

Substitute x=-3 into


F(x)=x*4-9x*3-8x*2-9x-2

Substitute


F(-3)=-3*4-9*(-3)*3-8*(-3)*2-9*(-3)-2

Determine the sign


F\left(-3\right)=-3*4+9*3*3+8*3*2+9*3-2

Calculate the product or quotient


F(-3)=-12+9*3*3+8*3*2+9*3-2


F\left(-3\right)=-12+27*3+8*3*2+9*3-2


F\left(-3\right)=-12+81+8*3*2+9*3-2


F\left(-3\right)=-12+81+24*2+9*3-2


F\left(-3\right)=-12+81+48+9*3-2


F\left(-3\right)=-12+81+48+27-2

Calculate the sum or difference


F(-3)=69+48+27-2


F(-3)=117+27-2\\F(-3)=144-2\\F(-3)=142

I hope this helps you

:)

User Orkun
by
5.0k points
14 votes

Answer:

Explanation:

f(x) = x⁴ - 9x³ - 8x² - 9x - 2

f(-3) = (-3)⁴ -9*(-3)³ - 8*(-3)² - 9*(-3) - 2

= 81 - 9*(-27) - 8*9 + 27 -2

= 81 + 243 - 72 + 27 - 2

= 277

User Izumi
by
4.7k points